Experimental analysis of free-standing and substrate-constrained Ga-doped ZnO nanostructured thermoelectric films - Aicha S. Lemine; Jolly Bhadra; Anton Popelka; Muni Raj Maurya; Kishor Kumar Sadasivuni; Rana Abdul Shakoor; Ahmad Zubair; Noora J. Al-Thani; Anwarul Hasan (Heliyon)
Developing thermoelectric films without substrates—free-standing films—eliminates substrate-induced effects on performance and meets the flexibility requirements of emerging wearable thermoelectric applications. This study investigates Gallium-doped Zinc Oxide (GZO), composed of abundant and non-toxic elements, to fabricate a substrate-free GZO film via 3D printing and compares its structural, chemical, and thermoelectric properties with those of a substrate-constrained GZO film produced through chemical deposition. Both films exhibited uniform crystal structures and phase purity; however, the substrate-constrained film displayed additional diffraction peaks, suggesting potential substrate interactions. The 3D-printed free-standing film effectively eliminated the tensile stresses observed in the substrate-constrained film. FE-STEM analysis revealed nanostructures with homogeneous elemental distribution in both films, though the substrate-constrained film showed discontinuities, such as pores, likely caused by post-deposition annealing treatment. XPS analysis highlighted differences in chemical states and elemental compositions between the films, influenced by fabrication methods, substrate-induced stresses, and surface energy mismatches. The free-standing GZO film developed through 3D printing exhibited a more balanced incorporation of Zn and O, as it was not subject to substrate or post-deposition annealing constraints. Consequently, it demonstrated a 14 % increase in electrical conductivity and a 91 % improvement in the Seebeck coefficient compared to the substrate-constrained film, resulting in a higher room-temperature power factor of 261 nW/m·K2. These findings underscore the potential of 3D-printed free-standing GZO films to advance thermoelectric applications, offering a promising alternative to overcome the challenges of substrate-constrained films and further drive innovation in the field.